Identifying the underlying challenges that face doctoral education in chemistry. - Melissa A Collini; Benedicta Donkor; Jordan Harshman (PLoS ONE)
Doctoral education in chemistry (DEC) in the United States is charged with producing scientists who are capable of addressing the world's Grand Challenges, enhancing quality of life and innovation both domestically and globally through advanced science. However, many believe these doctoral programs are failing to adequately and equitably prepare students for those responsibilities. While numerous challenges have been identified, many are based in perspective and opinion rather than inferred from theory-driven education research. This is problematic as it does not give evidence-based insight into the challenges facing DEC. This qualitative research study aims to address this issue by answering the research question: What are the issues and challenges within doctoral education in chemistry from the faculty perspective? This will be accomplished by interviewing faculty members of chemistry PhD programs and analyzing these interviews to characterize the challenges undermining DEC in the United States. Our findings indicate that there are four main themes characterizing these challenges: 1) universities and faculty struggle to find balance between multiple responsibilities; 2) there are no standard or robust assessments to assess student outcomes; 3) the implementation of many programmatic elements is ineffectual; and 4) inadequacies and inconsistencies with mentorship are deeply problematic. Research implications for these findings are significant as they give insight into the underlying, systemic challenges that face DEC, rather than simply identifying symptomatic, surface-level issues. This lays the foundation for future research addressing challenges facing DEC. Our results are presented to equip those looking to reform doctoral education with essential insights needed to understand and begin addressing the aforementioned areas of concern.